Ascenção e queda do provimento de acesso gratuito à Internet no Brasil: o papel dos modelos de negócio - Santos, Sérgio Ricardo Yates dos (2002)
This research was commenced with the idea to promote an strategic evaluation of the sustentability of the free Internet access, analysing its process of value creation, its sources of revenue generation, its business models development as well as its capacity to generate adequated returns to the investors. It was concluded that the free Internet access is not dead. Indeed, what has occoured was a migration from a model completely based on delivering a single service, generally dependent of publicity sells revenues, to a hibrid based business model with different types of services and with revenues been generated from multiple sources. Nevertheless, not all players were capable to evolute their business models and survive, what occasioned a huge number of fails, mergers and acquisitions, resulting in a concentration all over the segment.